Pharmacological and Therapeutic Properties of Punica granatum Phytochemicals: Possible Roles in Breast Cancer - Moga Marius Alexandru; Dimienescu Oana Gabriela; Balan Andreea; Dima Lorena; Toma Sebastian Ionut; Bigiu Nicusor Florin; Blidaru Alexandru (Molecules, 2021)
Background: Pomgranate (Punica granatum) represents a high source of polyphenols with great bioavailability. The role of this fruit in the prevention and treatment of various malignant pathologies has been long time cited in both scientific and non-scientific literature, making thus important to identify its involvement in the pathophysiological processes. The treatment for breast cancer had focused on the inhibition of the mechanisms that governs the estrogen activity. These mechanisms are covered either by the antagonism of the estrogen receptor (ER) or by the inhibition of the estrogen synthesis. Our interest in identifying a bioactive compound rich in polyphenols, which induces both the antagonism of the estrogen receptor, and the inhibition of the estrogen synthesis, revealed us the pomegranate fruit and its derivatives: peel and seeds. Pomegranates’ chemical composition include many biological active substances such as flavonols, flavanols, anthocyanins, proanthocyanidins, ellagitannins and gallotannins. Materials and Methods: We performed a review of the scientific literature by using the following keywords: “pomegranate”, “breast cancer”, “Punica granatum”, “pomegranate polyphenols”. Our search was performed in the PubMed and Google Scholar databases, and it included only original research written in English from the last 20 years. None of the articles were excluded due to affiliation. A total number of 28 original papers, which mentioned the beneficial activity of pomegranate against breast cancer, were selected. Both clinical and preclinical studies were considered for this review. Results: Recent discoveries pointed out that polyphenols from Punica granatum possess strong anti-cancer activity, exhibited by a variety of mechanisms, such as anti-estrogenic, anti-proliferative, anti-angiogenetic, anti-inflammatory, and anti-metastatic. Pomegranate extracts induced cell cycle arrest in the G0/G1 phase, and induced cytotoxicity in a dose- and time-dependent manner. Moreover, several polyphenols extracted from pomegranate inhibited the invasion potential, migration and viability of breast cancer cells. The effects of pomegranate juice on serum estrogens and other sexual hormones levels were also investigated on two human cohorts. Conclusions: Punica granatum represents a promising area in oncology. The large availability and low cost, associated with the lack of side effects, made from this natural product a great strategy for the management of breast cancer. There are several mechanistic studies in mouse models and in breast cancer cell lines, suggesting the possible pathways through which polyphenols from pomegranate extracts act, but larger and better-controlled studies are necessary in the future. Only two small clinical trials were conducted on humans until now, but their results are contradictory and should be considered preliminary.
Keywords: breast cancer; pomegranate; Punica granatum; pomegranate polyphenols